Single-band zigzag dipole artificial magnetic conductor - Abu, M. (Penerbit UTM Press, 2012)
A new Artificial Magnetic Conductor (AMC) structure called zigzag dipole is discussed. Based on the 0.92GHz straight dipole AMC, the zigzag dipole AMC operating at 0.92GHz, 2.45GHz and 5.8GHz are carried out using TLC-32 and RF-35 boards. This AMC structure is designed based on the characterization of a unit cell using a transient solver of Computer Simulation Technology (CST) software. The simulated results such as the reflection phase, reflection magnitude, surface impedance, bandgap and electric field for each single-band AMC are presented in this paper. From the results gained it shows that, the bandwidth of the AMC will increase when the frequency is increased. It is also proved that these AMC are not providing the bandgap at their resonance. The zigzag dipole AMC is carried out to minimize the AMC size and to be suitable for UHF RFID applications.